Photochemical determination of the interactions between surfactants and polyelectrolytes - Neumann, Miguel G.; Tiera, Marcio J. (De Gruyter, 1997)
The interaction of polyelectrolytes with oppositely charged ionic surfactants was studied at low surfactant concentrations using photochemical bound and free probes. Free probes migrate to initially formed pre-aggregates in systems with high charge- density polyelectrolytes, giving rise to excimer emission. For these systems the initial aggregation process seems to be due to electrostatic interactions. For larger surfactants or copolymers containing larger proportions of neutral monomer that interactions are of hydrophobic nature.